INTERNATIONAL INITIATIVES OF THE SCIENTIFIC COMMUNITY OF PSYCHOLOGISTS OF ARMENIA (7th INTERNATIONAL CONFERENCE "ACTUAL ISSUES OF THEORETICAL AND APPLIED PSYCHOLOGY") - AVANESYAN, HRANT (Bulletin of Yerevan University E: Philosophy, Psychology, 2020)
.